Empathy in schizophrenia: neural alterations during emotion recognition and affective sharing - Knobloch, Simon; Leiding, Delia; Wagels, Lisa; Regenbogen, Christina; Kellermann, Thilo; Mathiak, Klaus; Schneider, Frank; Derntl, Birgit; Habel, Ute (Frontiers in Psychiatry, 2024)
Deficits in emotion recognition and processing are characteristic for patients with schizophrenia [SCZ]. We targeted both emotion recognition and affective sharing, one in static and one in dynamic facial stimuli, during functional magnetic resonance imaging [fMRI] in 22 SCZ patients and 22 matched healthy controls [HC]. Current symptomatology and cognitive deficits were assessed as potential influencing factors. Behaviorally, patients only showed a prolonged response-time in age-discrimination trials. For emotion-processing trials patients showed a difference in neural response, without an observable behavioral correlate.‘ During emotion and age recognition in static stimuli a reduced activation of the bilateral anterior cingulate cortex [ACC] and the right anterior insula [AI] emerged. In the affective sharing task, patients showed a reduced activation in left and right caudate nucleus, right AI and inferior frontal gyrus [IFG], right cerebellum and left thalamus, key areas of empathy. We conclude that patients have deficits in complex visual information processing regardless of emotional content on a behavioral level and that these deficits coincide with aberrant neural activation patterns in emotion processing networks. The right AI as an integrator of these networks plays a key role in these aberrant neural activation patterns and, thus, is a promising candidate area for neurofeedback approaches.